Highly porous Zr-MCM-48 immobilized Cu-porphyrin for photocatalytic reduction of CO2 to methanol in a slurry reactor - Nadeem, S. (Springer, 2021)
This study involves the development of novel mesoporous Zr-MCM-48 photocatalyst impregnated with Cu-porphyrin (CuTPP) having Si/Zr ratio of 100, 50 and 25. The synthesized materials were applied as hybrid photocatalyst affording mid-gap energy states and Zi3+ sites for reduction of CO2 into methanol selectively using UVâVisible light treatment. Interestingly, Zr-MCM-48 displayed significant photocatalytic reduction ability under UVâVis wavelength. The bare Zr-based MCM-48(25) matrix with maximum Zr content in catalyst enhanced the photocatalytic activity with 47.5Â Âµmol methanol formation, possessing high surface area SBET of 1324Â m2Â gâ1, under UVâVisible light irradiation. The characterization results highlighted the influence of visible light active Cu-porphyrin interaction over Zr-MCM-48 silica frameworks due to transition of electrons from the porphyrin centres to the active Zr sites as evident from DRS analysis. Moreover, the impregnation of Cu-porphyrin over Zr-MCM-48(25) displayed methanol formation about 365.11Â Âµmol under UVâVisible light using 0.1Â M NaOH and 0.1Â M Na2SO3. Also, the effect of varying reaction conditions shown that catalyst concentration, metal loading, light intensity and stirring speed pronouncedly impact the formation of methanol. Â© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.